2018
DOI: 10.3390/met8020119
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Metal Magnetic Memory Testing of 35CrMo Steel during Fatigue Loading

Abstract: Abstract:The fatigue fracture of a drillstring could cause drilling disturbances and some negative impacts (e.g., economic loss) will be brought when restoring the drillstring to functionality. In order to evaluate the effects of the fatigue damage of the drillstring during drilling, a new apparatus, which could monitor the load level in real-time, was built to perform the four-point bending fatigue test on 35CrMo steel, a typical material of drillstrings. Such an apparatus is based on metal magnetic memory (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Sensing elements able to monitor surface stresses in steels can be those monitoring localized changes of sound velocity, including the use of non-linear acoustics [11], electromagnetic properties such as eddy currents for resistivity and impedance determination [12], optical properties using the Kerr effect [13], as well as magnetic properties like surface permeability in the magnetic stress calibration curve (MASC) technique [14] and the magnetic memory method (MMM) [15], or magnetic Barkhausen noise method [16]. The sensing elements used in acoustic techniques offer a spatial resolution in the order of cm and may be used in industrial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Sensing elements able to monitor surface stresses in steels can be those monitoring localized changes of sound velocity, including the use of non-linear acoustics [11], electromagnetic properties such as eddy currents for resistivity and impedance determination [12], optical properties using the Kerr effect [13], as well as magnetic properties like surface permeability in the magnetic stress calibration curve (MASC) technique [14] and the magnetic memory method (MMM) [15], or magnetic Barkhausen noise method [16]. The sensing elements used in acoustic techniques offer a spatial resolution in the order of cm and may be used in industrial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Huang [14] and Li [15] investigated the relationship between crack length and gradient of H y by carrying fatigue bending tests. Chowdhury [16] and Hu [17] also investigated the mechanisms of fatigue crack growth and studied the magnetic field variation. In previous studies, the variations of magnetic signals in different stages of the fatigue process were not deeply discussed or fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring the fatigue damage of the civil engineering structures has been actively investigated [ 6 , 7 , 8 ]. The current methods for monitoring the fatigue damage mainly include Barkhausen noise measurements [ 9 , 10 , 11 , 12 ], X-ray tomography [ 13 , 14 , 15 , 16 ], metal magnetic memory (MMM) testing method [ 17 , 18 , 19 , 20 , 21 ], acoustic emission (AE) [ 22 , 23 , 24 , 25 ], ultrasonic and nonlinear ultrasonic techniques [ 26 , 27 , 28 , 29 , 30 ], among others. Barkhausen noise measurements were used to evaluate fatigue damage of engineering structural steel structures [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marrow et al demonstrated the feasibility of imaging short fatigue cracks with high resolution synchrotron X-ray tomography [ 13 , 14 ]. The metal magnetic memory testing method is a novel nondestructive testing technology developed to monitor crack propagation and predict fatigue life [ 17 , 18 ]. The acoustic emission (AE) monitoring has been developed as an effective method for the detection, location and monitoring of fatigue damage in the metal structures by monitoring the acoustic signature of the fatigue crack during the opening/closing process [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%